Terjebak Simbol, Tertinggal Akses: Analisis Multiperspektif Hambatan Sistemik dalam Perbankan Syariah di Kota Padang - Divana Yuliant (UIN AM. Sangadji Ambon, 2025)
This study aims to identify systemic barriers hindering the development of Islamic banking in Padang City through a qualitative, multiperspective approach. Primary data were collected via in-depth interviews with key stakeholders, including regulators (OJK, BI, MUI), practitioners (BSI, BTN Syariah), academics, and customers. Thematic analysis, supported by NVivo 12 Plus, revealed four major challenges: suboptimal digitalization, low levels of public understanding and financial literacy, limited-service infrastructure, and negative public perception of Islamic banking. Based on these findings, the study proposes three strategic recommendations: enhancing community-based public education, expanding the reach of service infrastructure, and optimizing integrated digital transformation. The novelty of this research lies in its grounded, multi-stakeholder field approach, offering a contextual and actionable understanding of the systemic challenges faced by Islamic banking in Muslim-majority regions. Keywords: Islamic banking; literacy; digitalization; Padang City; multiperspective